A study on awareness among final year students of UiTM Malacca City Campus towards Takaful career / Filzah Wahidah Abdullah Sani and Syarifah Ummu Athirah Sayed Yusoff - Abdullah Sani, Filzah Wahidah; Sayed Yusoff, Syarifah Ummu Athirah (Faculty of Business and Management, 2013)
Takaful products are “sold and not bought”. Only a few participants voluntarily come to Takaful operators to participate into the Takaful schemes. Hence, Takaful operators have to depend on aggressive agents as one main human capital development in takaful Industry that willing to consult, explain and convince the potential participants about Takaful systems and schemes. The increasing number of agents from year to year show that agent’s service become important today. There is an issue explained that the Islamic Insurance agent has a strong point to manage insurance products that meet the Shariah criteria. In this study, this study focuses on final year students of UiTM Malacca City Campus to know whether they are aware about Takaful career. Hence, Convenience sampling is being used. 100 Questionnaires have been answered by the targeted respondents. Using the descriptive statistics, Pearson’s Correlation and regression has been used to determine whether there are relationships between dependent variables and independent variables. There are findings that proves about there are positive relationships between awareness of Takaful career and knowledge, financial expectation and benefits. The most influence factor of awareness towards Takaful career is benefits.